Recommencing lithium in Older Adults with Bipolar I Disorder. (December 2017) - Gallur, Lara; Powell, Alice; Flynn, Patrick
Objectives: This paper addresses considerations in recommencing lithium in elderly patients with Bipolar I Disorder and medical comorbidity. We focus on nephrotoxicity and cognitive impairment. Methods: Case reports and review of relevant literature. Results: Three elderly psychogeriatric inpatients admitted with severe manic relapse following lithium cessation are described. In all cases, lithium was recommenced safely with good response. Conclusions: Even with medical comorbidity it may be possible to recommence modified lithium therapy.